Der Einfluss des Aktivierenden Staates auf Familienpolitik in Deutschland und den Niederlanden - Willenborg, Ansgar (Q-Serie, 2011)
This dissertation investigates the influence of the political-administrative ideal of the 'activating state' on German and Dutch family policy. It is studied to what extent parallels can be discerned between the family policies that are pursued by these two countries. It is clarified how the aforementioned ideal is converted into family policy, whilst also offering an answer to the question whether any convergences exist in the field of family policy as pursued within the European Union. In order to be able to answer this question, an ideal model for activating family policy has been created to facilitate a comparison between the two countries. This involves an inductive method in which the divergences and convergences of both countries have been worked out in greater detail. In view of the development of the ideal model, Bandemer's indicators for the 'activating state' are studied in combination with Kaufmann's family policy goals and instruments, and Esping-Andersen's state intervention typologies for family policy. This is followed by a specification of the family policy goals and instruments based on an analysis of various documents. The goal of this investigation is to concretise the concept of activating family policy. Additionally, it is shown which 'activating strategies' have been used by both countries and how they have translated the ideal of an activating state. Not only does this offer an answer to the theoretical question about the use of activating policies in areas other than the often-evaluated labour market policies, but it also provides an overview of various activating examples. Using an analysis of the investigated instruments and the corresponding literature, a number of conclusions have been formulated about the convergences and divergences in the family policies that are pursued by these two countries. The dissertation ends with an assessment of the ideal's gaps and shortcomings and a discussion about its possible further development.